Cameroon’s cinematographic policy from 1962 to 1973: Between awareness and stuttering - TAYONG FOTSA , Jospin Odilon (Revue Internationale du Chercheur, 2025)
Abstract On January 01rst 1960, East Cameroon, formerly under French administration, became independent. As a sovereign state, it now had the capacity to define the major political, economic and socio-cultural orientations that would facilitate and accelerate its development. It was in this context that the public authorities became aware of the multiple potentials of the Movie industry. To structure it, an early-stage film policy was implemented. The basis of this strategy was the creation of institutions specifically dedicated to the promotion of the seventh art (filmmaking). This policy really took shape with the creation of the first national film body in 1962. The most important of these institutions was the Film Industry Development Fund (FODIC in French), which was birthed on October 27th 1973. However, between the two periods, a number of initiatives were undertaken to boost the industry. This article examines the highlights of the film policy implemented by the State of Cameroon between 1962 and 1973.